1998
DOI: 10.1111/j.1398-9995.1998.tb03973.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergy to bumblebee venom. II IgE cross‐reactivity between bumblebee and honeybee venom

Abstract: To obtain more information on IgE cross‐reactivity between bumblebee venom and honeybee venom, we tested sera from venom‐sensitized patients for specific IgE against venoms from the European bumblebee (Bombus terrestris), the North American bumblebee (Megabombm pennsylvanicus), and the honeybee (Apis mellifera). RAST, RAST‐inhibition, and immunoblotting experiments indicate that bumblebee venom and honeybee venom contain venom‐specific IgE‐binding epitopes. These results suggest that immunotherapy using honeyb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 22 publications
0
11
0
1
Order By: Relevance
“…There is limited IgE cross‐reactivity between wasp/hornet and paper wasp venom [31]. Venoms from bumble bee and honey bee are highly cross‐reactive clinically which is consistent with the degree of structural homology found in the enzymes [36, 37]. About 75% of sera from patients allergic to honey bee venom react to in vitro tests with bumble bee venom, and 85% of sera from patients with a history of allergy to bumble bee stings demonstrate positive tests to honey bee venom [37].…”
Section: Venom Allergensmentioning
confidence: 81%
“…There is limited IgE cross‐reactivity between wasp/hornet and paper wasp venom [31]. Venoms from bumble bee and honey bee are highly cross‐reactive clinically which is consistent with the degree of structural homology found in the enzymes [36, 37]. About 75% of sera from patients allergic to honey bee venom react to in vitro tests with bumble bee venom, and 85% of sera from patients with a history of allergy to bumble bee stings demonstrate positive tests to honey bee venom [37].…”
Section: Venom Allergensmentioning
confidence: 81%
“…venom-based VIT in patients with hornet venom allergy [27]. 'RAST'-inhibition tests and immunoblotting experiments, however, revealed biochemical differences between bumblebee and honeybee venom and also between European (Bombus terrestris) and American (Megabombus pennsylvanicus) bumblebees [28]. There are also differences regarding the composition of European and American Polistes spp.…”
Section: Venom For Specific Immunotherapymentioning
confidence: 98%
“…Although these allergens from both species are similar, they contain different IgE-reactive epitopes (Hoffman et al, 2001). Also others reported that differences in IgE-binding between venoms of both species exist (Stapel et al, 1998). Further research is needed to determine whether this diversity in venom composition is also true for the other 250 bumblebee species (Williams et al, 2008).…”
Section: Consequences For Hymenoptera Venom Allergy Diagnosismentioning
confidence: 95%